An empirical study of the effects of conscientiousness in pair programming using the five-factor personality model - Salleh, Norsaremah; Mendes, Emilia; Grundy, John; Burch, Giles St. J. (ACM Press, 2010)
This paper describes a formal experiment carried out to investigate the effect of the Personality factor conscientiousness on the effectiveness of Pair Programming as a pedagogical tool in higher Education. This experiment took place at the University of Auckland, using as subjects undergraduate students attending an introductory programming course. Conscientiousness was chosen because it has been shown to be the most consistent predictor of academic achievement. Our findings showed that differences in conscientiousness level did not significantly affect the academic performance of students who pair programmed, which could have been due to the short duration of the tasks used throughout the experiment. However, results revealed that another Personality factor - Openness to experience - presented a significant correlation with paired students’ academic performance.